2008
DOI: 10.5771/0340-1758-2008-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Mythen und Methoden. Zur Messung der Europäisierung der Gesetzgebung des Deutschen Bundestages jenseits des 80-Prozent-Mythos

Abstract: Zu den Triebkräften, die "Transformationen des Staates" 1 hervorgebracht haben und weiter hervorbringen, gehören insbesondere Globalisierung und europäische Integration. Letztere ging in den vergangenen zwanzig Jahren mit der Bildung eigenständiger Institutionen der Europäischen Gemeinschaft beziehungsweise der Union und der Übertragung immer weiterer Kompetenzen auf die Union einher. Die Nutzung der an diese übertragenen Regelungskompetenzen durch die Gemeinschaft mag zwar insgesamt häufi g zu einer Steigerun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 1 publication
0
11
0
5
Order By: Relevance
“…25 Research has shown this share to be much lower, even when including domestic laws that were in some way 'inspired' by the EU. For example, Töller (2008) demonstrates that while the share of EU-inspired legislation enacted by the German Bundestag has more than doubled since the mid-1980s, in the 15th election period (2002 -05) 39 per cent of the laws were influenced by a 'European impulse'. Empirical studies on the UK, the Netherlands, Denmark, Sweden, and Finland indicate that the share of EU-related laws is between 10 and 40 per cent, depending on the operationalisation of 'EU-related' legislation.…”
Section: Measuring the Europeanisation Of National Legislaturesmentioning
confidence: 97%
See 1 more Smart Citation
“…25 Research has shown this share to be much lower, even when including domestic laws that were in some way 'inspired' by the EU. For example, Töller (2008) demonstrates that while the share of EU-inspired legislation enacted by the German Bundestag has more than doubled since the mid-1980s, in the 15th election period (2002 -05) 39 per cent of the laws were influenced by a 'European impulse'. Empirical studies on the UK, the Netherlands, Denmark, Sweden, and Finland indicate that the share of EU-related laws is between 10 and 40 per cent, depending on the operationalisation of 'EU-related' legislation.…”
Section: Measuring the Europeanisation Of National Legislaturesmentioning
confidence: 97%
“…26. For a review of this literature and a thoughtful discussion on the methodological problems and how to overcome them, see Töller (2007Töller ( , 2008. 27.…”
Section: Note On the Authormentioning
confidence: 99%
“…The main message here is that legal Europeanization (measured by the number of national rules that have a European imprint) in each country is limited, in mid‐2003, to less than 15 per cent of all rules in force. Studies of legislation in Austria (Jenny and Müller 2010) and Germany (Töller 2008) that measure the dynamics of the Europeanization process rather than its consequences for the entire body of national legislation, support the magnitude of this result.…”
Section: Eu Impact On National Regulatory Regimes: Global Resultsmentioning
confidence: 99%
“…EU regulatory policies in general correspond to the national allocation of policy portfolios, and EU regulatory demands have widely been accommodated within domestic political and administrative procedures. Still, these complexities raise a series of methodological issues to be thoroughly discussed before we can develop a valid measure of Europeanization to be used in broader comparative studies (see Töller 2007; 2008; Moravcsik and Töller 2007).…”
Section: Advances In the Study Of The European Unionmentioning
confidence: 99%